Perceived stress, psychological well-being and burnout among female nurses working in government hospitals - K J, Divinakumar; Pookala, Shivram Bhat; Das, Ram Chandra (International Journal of Research in Medical Sciences, 2017)
Background: Few studies have studied about the Burnout among government employed Female Nurses in India. Methods: A cross sectional survey was done by mailing questionnaires containing Perceived Stress Scale (PSS-10), Copenhagen Burnout Inventory (CBI) and General Health Questionnaire (GHQ-28) to all 603 Nurses posted in thirty government hospitals of central India. Fifty seven percent responded and 298 valid questionnaires were analysed. Results: Sixty three nurses (21%) had GHQ 28 score more than 4 indicative of psychological distress. One hundred and forty four nurses (48.32%) had perceived stress scores above 17 in PSS -10. Age and Service were found to be negatively correlated with stress and burnout (p<0.04). Proportions of the nurses with a ‘high degree of burnout’ (defined as >50 points on a scale of 0-100) were 27.2%, 14.7%, and 9.4% respectively for Personal, Work and Client related Burnout categories. More nurses employed in ICU, maternity ward, General Family Ward, Surgical wards, and Medical wards had work related burnout when compared to those in Administration, Emergency Room and VIP Wards. No significant differences were observed in the scores of GHQ-28, PSS-10 and CBI when the nurses were compared on the basis of their marital status or educational achievements. Conclusions: Prevalence of Burnout in government employed Female Nurses in India was less when compared to prevalence of burnout in nurses reported in western countries. The perceived Stress and Burnout was more in Nurses of 31-50 years age group, and being employed in the acute wards.